Russkaia pravoslavnaia tserkov' : soglasie i inakomyslie - Dzhein Ellis ; perevod s angliiskogo Georgiia Sidorenko. (Overseas Publications Interchange Ltd, 1990)
First published in English as Part 2 of "The Russian Orthodox Church: A Contemporary History", Croom Helm, London & Sydney, 1986.Includes bibliographical references and index.